2004
DOI: 10.1007/s00394-004-0481-3
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of vitamins C and E increases the vitamin E status but does not prevent the formation of oxysterols in the liver of guinea pigs fed an oxidised fat

Abstract: The results demonstrated that supplementation of vitamins E and C improves the vitamin E status but does not prevent the formation of lipid oxidation products in the liver of guinea pigs fed oxidised fats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The finding that the body weight development was not affected by the oxidized fat is advantageous from a methodological viewpoint because the effects of the oxidized fat were not confounded by secondary effects of reduced growth. Recent studies have shown that consumption of oxidized fats leads to a reduction of tocopherol concentrations in animal tissues due to a reduced digestibility and an enhanced turnover of vitamin E [8,11,12,43]. The finding of reduced α-tocopherol concentrations in plasma and liver of pigs fed the oxidized fat in the present study indicates that even moderately oxidized fats compromise tissue vitamin E status in animals.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The finding that the body weight development was not affected by the oxidized fat is advantageous from a methodological viewpoint because the effects of the oxidized fat were not confounded by secondary effects of reduced growth. Recent studies have shown that consumption of oxidized fats leads to a reduction of tocopherol concentrations in animal tissues due to a reduced digestibility and an enhanced turnover of vitamin E [8,11,12,43]. The finding of reduced α-tocopherol concentrations in plasma and liver of pigs fed the oxidized fat in the present study indicates that even moderately oxidized fats compromise tissue vitamin E status in animals.…”
Section: Discussionsupporting
confidence: 61%
“…One of the most striking effects of oxidized fat is the induction of oxidative stress which is due to lipid hydroperoxides absorbed from the ingested oxidized fats and reactive oxygen species (ROS) generated from microsomal cytochrome P450 enzymes which are induced by oxidized fat [6-8]. Oxidative stress in animals fed oxidized fats is evident by elevated concentrations of lipid peroxidation products, reduced concentrations of exogenous and endogenous antioxidants, and a decreased ratio of reduced and oxidized glutathione in plasma and tissues [8-13]. …”
Section: Introductionmentioning
confidence: 99%
“…Although oxidized fat had no effect on proto-oncogene expression in fetal livers in the present study, oxidized fats might be considered critically in view of inducing oxidative stress in different tissues as shown in recent studies [36,37]. In addition, specific components of oxidized fats such as cyclic fatty acid monomers, which are formed in substantial amounts during domestic frying of frozen foods in sunflower oil [38], are probably toxic, e.g.…”
Section: Discussionmentioning
confidence: 58%
“…A more recent study, moreover, demonstrated that an oxidized fat prepared under deep‐frying conditions causes activation of PPARα in the liver and the vasculature and inhibits atherosclerotic plaque development in the low‐density lipoprotein receptor deficient mouse model of atherosclerosis 76. Although these findings show that oxidized fats exert some beneficial effects, they must not be interpreted in that way that oxidized fats are generally regarded as a health‐promoting component of the diet because oxidized fats were also reported to cause adverse effects 3–6, 8, 10. They rather suggest that oxidized fats are a mixture of chemically distinct substances, some of which exhibit potent regulatory activity on lipid metabolism.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Feeding experiments with rats, guinea pigs, and pigs revealed that ingestion of oxidized fats provokes various effects such as depletion of antioxidants, increase in lipid peroxidation 3–9, impairment of glucose tolerance 10, and alterations of thyroid hormone homeostasis 11–13. In addition, a great number of studies showed that oxidized fats influence lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%